2015
DOI: 10.1039/c5ra17623a
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol acetins: fuel additive synthesis by acetylation and esterification of glycerol using cesium phosphotungstate catalyst

Abstract: Glycerol acetylation and esterification reactions with acetic anhydride and acetic acid respectively give acetins, in which di and tri acetins are commercially important products used as fuel additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 37 publications
2
38
0
1
Order By: Relevance
“…The protonated acetic acid is then attacked by the oxygen of glycerol, forming monoacetin with the loss of one water molecule. The monoacetin formed gives diacetin and triacetin in a series reaction (Sandesh et al, 2015). % was achieved at the glycerol/acetic acid ratio of 1:10.…”
Section: Effect Of Reactants Molar Ratiomentioning
confidence: 95%
“…The protonated acetic acid is then attacked by the oxygen of glycerol, forming monoacetin with the loss of one water molecule. The monoacetin formed gives diacetin and triacetin in a series reaction (Sandesh et al, 2015). % was achieved at the glycerol/acetic acid ratio of 1:10.…”
Section: Effect Of Reactants Molar Ratiomentioning
confidence: 95%
“…The fundamental reaction pathway of esterification of glycerol with acetic acid involves the Fischer esterification mechanism [1,2]. Kale et al and Sandesh and co-workers reported that over ion exchange resins possesing high acidity, the addition of proton to the carbonyl oxygen takes place (Figure 7b), which generates positive charge on the carbonyl carbon and facilites the nucleophilic attack of hydroxyl group from glycerol [8,39]. They also reported that monoacetin is produced and subsequently diacetin and triacetin are observed in the consecutive steps, producing water as a by-product.…”
Section: Influence Of Reaction Conditions: Effect Of the Reaction Timmentioning
confidence: 99%
“…This could be explained by the fact that the presence of a higher amount of Brønsted acid sites (A15 catalyst) in reaction mix could augment CA conversion; nevertheless, it has negatively influenced GMC selectivity. 21 Again, electromagnetic energy (UV-visible spectra) contributed by quartz-halogen radiator caused excitation and relocation of electron-hole pairs from the valence band to conduction band in NT-P25, thereby facilitating higher GMC selectivity and CA conversion simultaneously. The individual effect of Ti 4+ and H + ions at lower conversion below 20% could be observed from Figure 2d.…”
Section: Effect Of Catalystmentioning
confidence: 99%
“…However, it could be inferred from Table 3 that increase in Brønsted acidity (H + ) in ATO mixture deteriorated GMC selectivity, which indicated that monoester selectivity was predominantly controlled by Lewis acid catalytic sites. 21 Again, electromagnetic energy (UV-visible spectra) contributed by quartz-halogen radiator caused excitation and relocation of electron-hole pairs from the valence band to conduction band in NT-P25, thereby facilitating higher GMC selectivity and CA conversion simultaneously. 22 Moreover, ATO dosage also played an important role in improving GMC selectivity and CA conversion (Figure 2c).…”
Section: Effect Of Catalystmentioning
confidence: 99%